EPR study of paramagnetic centers in mesoporous titanium dioxide prepared by nitric acid oxidation of titanium carbide - Ovodok, Evgeni A.; Ivanovskaya, Maria I.; Poznyak, Sergey K.; Gaevskaya, Tatiana V.; Azarko, Igor I. (Journal of the Belarusian State University. Chemistry, 2017)
Paramagnetic defects and radical forms of impurities in titanium dioxide, prepared from TiC by nitric acid oxidation and subsequent calcination in different conditions, have been studied by EPR. The presence of NO2, NO22−, NО, O3– and·С ≡ paramagnetic species in the TiO2 powder annealed in air was found. Heat treatment of the as-prepared TiO2 in argon leads to the formation of Ti3+ ions and large amount of С-containing radicals, which are characteristic of amorphous carbon. Processes responsible for appearance of paramagnetic centers and radicals in the TiO2 samples during synthesis were considered.
Keywords: mesoporous TiO2; EPR; C- and N-containing paramagnetic centers